Backbiting jurisprudence in the islamic law - AL-JUBOURI, YAQDAN SAMI MUHAMMAD (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT Backbiting is one of the dangerous illnesses in Islamic society, its law has prohibited and forbidden it in the legal texts mentioned in the Holy Qur’an and the noble Prophet’s Sunnah. The opinions of the jurists are clear that backbiting is forbidden, as it is one of the fatal lessons in destroying and separating the Islamic community. The Islamic religion and its tolerant Sharia (law) call for respecting the human being, preserving his honor, and not wronging him by speaking among others and trying to diminish and reduce his own humanity features.RESUMEN La difamación es una de las enfermedades peligrosas de la sociedad islámica, ya que su ley la ha prohibido en los textos legales mencionados en el Sagrado Corán y la Sunnah del noble Profeta. Las opiniones de los juristas son claras: la difamación está prohibida, ya que es una de las lesiones fatales en la destrucción y separación de la comunidad islámica. La religión islámica y su tolerante Sharia (ley) exigen respetar al ser humano, preservar su honor y no injuriarlo hablando entre otros y tratando de disminuir y reducir sus propios rasgos de humanidad.